PERANCANGAN CETAK BIRU TEKNOLOGI INFORMASI MENGGUNAKAN COBIT DAN ENTERPRISE ARCHITECTURE PLANNING (Studi Kasus Bidang Pendidikan Sekolah) - Mira Musrini B; Aditia Muchlis; Nur Fitrianti F (Universitas Widyatama, 2021)
Utilization of Information Technology is not just a support, but a business solution for organizations or companies, Madrasah Aliyah (MA) Al-Inayah as one of the organizers in the field of formal education equivalent to Senior High School (SMA) has a problem that not all of its Information Technology is integrated with one another. other. Because the utilization of Information Technology is not optimal yet, we need a framework that can develop an integrated Information Technology environment. In this study, an EAP (Enterprise Architecture Planning) framework was used to design an Enterprise Architecture and Control Objectives for Information and Related Technology (COBIT) 4.1 in measuring the maturity level of the use of Information Technology. The first stage in this research is to measure the maturity of the use of Information Technology, by distributing questionnaires based on questions on domains or objective controls, namely PO2 and PO3. The results of this Information Technology maturity assessment are evaluated based on the maturity gap that the organization wants to achieve and becomes a reference for Enterprise Architecture design. The results of this design can describe the Information Technology blueprint model along with the implementation roadmap which becomes a reference and guideline for preparing Information Technology blueprint documents.